(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper makes the case for the use of fantasy in exploring feelings of despair (contra Kierkegaard). I suggest that we adopt an existential-psychotherapeutic attitude towards the actuality of our (de)spero (despair/hope) and through the experience of balancing (de)spero, find liberation from, and peace within, our despair.